Public stigma toward fatigue—do social characteristics of affected persons matter? Results from the SOMA.SOC study - von dem Knesebeck, Olaf; Barbek, Rieke (Frontiers in Psychology, 2023)
Objectives: Although public stigma imposes a great burden on those affected with manifold negative consequence there is not much known about public stigma related to fatigue. Therefore, this study addresses the following research questions: 1) What is the magnitude of public stigma towards individuals with fatigue? 2) Are there differences in public stigma depending on the social characteristics of the affected person (sex, occupation, and migration)?Methods: Analyses are based on a national telephone survey in Germany (N=1,209). A vignette describing a person with symptoms of fatigue was presented to the respondents. Vignettes were varied according to sex, occupational status, and migration status. Stigma towards the person presented in the vignette was measured by stereotypes and negative emotional reactions (anger).Of the stereotypes under study, 'hypersensitive' was most frequently endorsed by the respondents (35.7%), followed by 'weak will' (27.2%). About 15% to 20% of the respondents agreed that they react with anger, annoyance or incomprehension. There were considerable differences in fatigue stigma according to the social characteristics of the affected person. In two social groups public stigma was particularly pronounced: (1) male persons with a low occupational status and a migration background; (2) female persons with a high occupational status and without a migration status. In contrast, women with a low occupational status and a migration background were less stigmatized.Individuals suffering from fatigue symptoms are confronted with stereotypes and negative emotional reactions by the public. Magnitude of public stigma considerably varies according to social characteristics of the afflicted person. Future studies should consider applying an intersectional approach to identify groups that are at risk of multiple stigma.